Expression of androgen-producing enzyme genes and testosterone concentration in Angus and Nellore heifers with high and low ovarian follicle count - Loureiro, Bárbara; Ereno, Ronaldo L. [UNESP]; Favoreto, Mauricio G.; Barros, Ciro M. [UNESP] (Elsevier, 2015)
Follicle population is important when animals are used in assisted reproductive programs. Bos indicus animals have more follicles per follicular wave than Bos taurus animals. On the other hand, B taurus animals present better fertility when compared with B indicus animals. Androgens are positively related with the number of antral follicles; moreover, they increase growth factor expression in granulose cells and oocytes. Experimentation was designed to compare testosterone concentration in plasma, and follicular fluid and androgen enzymes mRNA expression (CYP11A1, CYP17A1, 3BHSD, and 17BHSD) in follicles from Angus and Nellore heifers. Heifers were assigned into two groups according to the number of follicles: low and high follicle count groups. Increased testosterone concentration was measured in both plasma and follicular fluid of Angus heifers. However, there was no difference within groups. Expression of CYP11A1 gene was higher in follicles from Angus heifers; however, there was no difference within groups. Expression of CYP17A1, 3BHSD, and 17BHSD genes was higher in follicles from Nellore heifers, and expression of CYP17A1 and 3BHSD genes was also higher in HFC groups from both breeds. It was found that Nellore heifers have more antral follicles than Angus heifers. Testosterone concentration was higher in Angus heifers; this increase could be associated with the increased mRNA expression of CYP11A1. Increased expression of androgen-producing enzyme genes (CYP17A1, 3BHSD, and 17BHSD) was detected in Nellore heifers. It can be suggested that testosterone is acting through different mechanisms to increase follicle development in Nellore and improve fertility in Angus heifers.
Keywords: Androgen enzymes; Follicle; Ovary; Testosterone